2022
DOI: 10.3390/v14081724
|View full text |Cite
|
Sign up to set email alerts
|

The T350G Variation of Human Papillomavirus 16 E6 Gene Prevails in Oropharyngeal Cancer from a Small Cohort of Greek Patients

Abstract: Recent trends have shown a dramatic rise in the incidence of oropharyngeal squamous cell carcinoma strongly associated with high-risk human papillomavirus (HPV) of type 16. The genetic variability of HPV16 has been extensively studied in cervical cancer but there are very limited published data concerning the genetic variations of this HPV type in oropharyngeal cancer. In the present study, the genetic variations of HPV16 E6 gene sequences originated from a small cohort of Greek patients diagnosed with orophar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Conversely, an Italian study reported a prevalence of 19.6% for African HPV16 variants in HNSCC samples, highlighting their relevance in the head and neck anatomical tumor site [30]. As seen before in CC studies, when focusing on specific viral genome regions, such as the E6 gene, the most frequent polymorphism reported in a small cohort of HNSCCs was T350G [35,37]. However, this finding needs further investigation to determine its impact on clinical outcomes.…”
Section: Hpv16 Variants and Head And Neck Tumormentioning
confidence: 86%
See 1 more Smart Citation
“…Conversely, an Italian study reported a prevalence of 19.6% for African HPV16 variants in HNSCC samples, highlighting their relevance in the head and neck anatomical tumor site [30]. As seen before in CC studies, when focusing on specific viral genome regions, such as the E6 gene, the most frequent polymorphism reported in a small cohort of HNSCCs was T350G [35,37]. However, this finding needs further investigation to determine its impact on clinical outcomes.…”
Section: Hpv16 Variants and Head And Neck Tumormentioning
confidence: 86%
“…A study conducted in Greece showed that 85% of HPV16 sequences detected in 40 specimens from subjects with HNSCC were clustered into the European sublineage A3, while the remaining 15% of HPV16 variants were related to sublineage D1 [ 35 ]. In another study on HPV16–positive OPSCCs performed in the USA, the A1 sublineage was associated with poor recurrence-free survival (RFS) [ 87 ].…”
Section: Hpv16 Variants and Head And Neck Tumormentioning
confidence: 99%
“…Work on hepatocyte biochemistry revealed that HCV and dengue virus, another hepatotropic virus, replication is associated with catecholamine biosynthesis [ 12 , 13 ]. The Special Issue concluded with the growing importance of HPV variants, such as the T350G variant, in the understudying of the pathobiology of oropharyngeal cancer [ 14 ], as well as the assessment of the prevalence rates of common viruses, such as papilloma, herpes, and pox viruses, on the skin of beach volley athletes [ 15 ].…”
mentioning
confidence: 99%